A revision of the spider genera Chaetopelma Ausserer 1871 and Nesiergus Simon 1903 (Araneae, Theraphosidae, Ischnocolinae) - Guadanucci, Jose Paulo L.; Gallon, Richard C. (Zootaxa, 2008)
Chaetopelma Ausserer 1871 and Nesiergus Simon 1903 are revised. Cratorrhagus Simon 1891 is considered a junior synonym of Chaetopelma. Cratorrhagus tetramerus (Simon 1873) and the female of Cratorrhagus concolor (Simon 1873) are conspecific with C. olivaceum (C. L. Koch 1841). Ischnocolus gracilis Ausserer 1871, Ischnocolus syriacus Ausserer 1871, Chaetopelma shabati Hassan 1950 and Ischnocolus jerusalemensis Smith 1990 are also treated here as junior synonyms of C. olivaceum. Chaetopelma adenense Simon 1890 is proposed as a junior synonym of Ischnocolus jickelii L. Koch 1875. Chaetopelma gardineri Hirst 1911 is transferred to Nesiergus. Hence, Chaetopelma comprises three valid species: C. olivaceum (C. L. Koch 1841); C. karlamani Vollmer 1997; C. concolor (Simon 1873) n. comb. from the Middle East and northeastern Africa. Nesiergus, which appears endemic to the Seychelles archipelago, now comprises three valid species: N. gardineri (Hirst 1911) n. comb.; N. halophilus Benoit 1978; N. insulanus Simon 1903.